THE CONSTITUTIONALITY OF THE ESTABLISHMENT OF THE LAW ON THE INSTITUTION OF THE PEOPLE'S CONSULTATIVE ASSEMBLY (MPR) OF THE REPUBLIC OF INDONESIA AS A FORM OF MANIFESTATION OF ARTICLE 2 PARAGRAPH (1) OF THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Monitasari, Restu Gusti (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study discusses two main problems: first, constitutional values in the institutional arrangements of People's Consultative Assembly of the Republic of Indonesia (MPR RI) based on the 1945 Constitution of the Republic of Indonesia in the development of legislation in Indonesia; second, the urgency of the establishment of the MPR RI Institutional Law as an implementation of Article 2 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The article states that "The People's Consultative Assembly consists of members of the People's Representative Council and the Regional Representative Council who are elected through general elections and further regulated by law." Therefore, a special law is needed to regulate the MPR, as also explained in the appendix to Law Number 12 of 2011. However, until now, the MPR institution is still regulated together with the House of Representatives (DPR), the Regional Representative Board (DPD), and the Regional House of Representatives (DPRD) in Law Number 2 of 2018 (UUMD3), which has the potential to cause confusion because the four institutions have different positions, functions, and authorities. This study uses a normative legal method with a descriptive analytical approach that is perspective in nature to provide solutions to the problems of state institutional arrangements in Indonesia. The results of the study show that based on Article 2 paragraph (1) of The 1945 Constitution of the Republic of Indonesia post- amendment, a special law is needed regarding the MPR institution. The regulation of the MPR in one joint legal product with DPR, DPD, and DPRD not only creates ambiguity in society, but also contradicts the characteristics of each institution from a historical, philosophical, sociological, and legal perspective. Therefore, it is necessary to establish a separate MPR Institutional Law from the UUMD3.